“Opening a Door to a New Life”: The Role of Forgiveness in Healing From Moral Injury - Purcell, Natalie; Griffin, Brandon J.; Burkman, Kristine; Maguen, Shira (Frontiers in Psychiatry, 2018)
For military veterans struggling with moral injury, forgiveness can become both an animating concern and a potential path to healing. In this perspective piece, we draw on our clinical work and research findings to examine why forgiveness matters to veterans who feel guilt and shame about their actions in war, what type of forgiveness is attainable and meaningful, and what role clinicians can play in facilitating forgiveness. We conclude by reflecting on the potential, as well as the limits and tensions, of forgiveness work in the context of military moral injury.